PENGARUH SERVICE RECOVERY TERHADAP TINGKAT KEPUASAN NASABAH DI BANK PANIN KCU PEMATANGSIANTAR - Nancy Florida Siagian; Henry Dunan Pardede; Hengki Mangiring Parulian Simarmata (Politeknik Bisnis Indonesia, 2021)
Service is very important factor in the service industry. Improving service quality can retain consumers and increase satisfaction. This study aims to examine and explain the magnitude of the effect of service recovery on customer satisfaction levels. The object of this research is Panin Bank KCU Pematangsiantar. This research is a quantitative study with a sample size of 97 customers using a purposive side. The collecting data method is using a questionnaire. The analysis technique uses a simple linear regression analysis model. Data are testing for validity test, reliability test, normality test, and coefficient of determination test. The results of the SPSS test showed that there was an effect of service recovery of 58.8% on satisfaction, and the remaining 41.7% influenced by other factors not examined in this study. The t-test shows that there is a signifikant positive effect on customer satisfaction. The results of this study are to provide information to management in making service improvement policies. For subsequent research, the research variables can be developed like service quality and customer relationship management